Study of sequential multipoint injection nozzle effect of compressed natural gas engine - Mohd Adib, Alias (2008)
The research and development of injection system has always been influenced by the availability and the form of fuel. In this project is about the study of the injection nozzle effect of compressed natural gas engine. This project study and simulate twenty types of sequential injection nozzle with different geometries using SolidWork and Cosmos FloWork software to find the best air and fuel mixing in the combustion chamber of the engine. The other effect of the modified injection nozzle is the velocities of the fuel in combustion chamber that can be determine using the software. The length of bore and stroke of the engine is base on the actual diesel engine and been model using SolidWork. As the result, the best injection nozzle is 10 degree nozzle. The air and fuel mixing is very good and better compare with the original injection nozzle. The velocity of fuel in combustion chamber is the highest compare with other design.